VD_FINDINFO Jug / 2015 / 249 vom 27. November 2014 - VD Tribunal cantonal (2014)
LÉSION CORPORELLE SIMPLE, ABUS D'AUTORITÉ, APPRÉCIATION DES PREUVES, ACQUITTEMENT | 123 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH)